Knowledge, attitude, and practices regarding miscarriage: A cross-sectional study among Flemish midwives. (January 2018) - De Roose, Marjon; Tency, Inge; Beeckman, Dimitri; Van Hecke, Ann; Verhaeghe, Sofie; Clays, Els
Abstract: Objective: to examine the knowledge, attitude and practices (KAP) of Flemish midwives regarding miscarriage. Design and setting: a cross-sectional KAP study was conducted in 28 hospitals in Flanders (Northern region of Belgium) from September 2015 to January 2016. Participants: a total of 647 out of 1200 midwives (53.9%) working on maternity, labour and gynaecological wards, maternal and neonatal (intensive) care units, antenatal consultations, and reproductive medicine were recruited. Measurements: data were collected using a semi-structured, self-administered questionnaire. Findings: the mean knowledge score was 6.31 out of 10. Of all participants, 47% recently cared for couples with miscarriage, and the majority (97%) indicated a key role for midwives in the psychosocial support of those couples. Lack of time, incapability and fear of being overwhelmed by their own feelings were identified as main barriers for psychosocial support. Knowledge was more often evaluated as adequate when miscarriage was included in the midwifery education (31% vs. 17.3%, χ 2 = 12.965, df = 1, p<0.001). Midwives trained for the topic 'miscarriage' more often valued their role in miscarriage care (98.8% vs. 94.1%, χ 2 = 11.002, df = 1, p = 0.001). They considered themselves being more capable to provide adequate psychosocial support when feeling sufficiently trained in communicative skills (77.7% vs. 33.8%, χ 2 = 96.574, df = 1, p<0.001). The majority (72.4%) indicated a lack of knowledge regarding miscarriage. Almost 89% expressed a need for extra training. Conclusions and implications for practice: midwives in Flanders assist in the care for couples with miscarriage and consider themselves as a key healthcare provider in the psychosocial support. This study highlighted several barriers regarding miscarriage care, e.g. a lack of knowledge and incapability. Adequate training in knowledge and communication skills is important and necessary in order to promote appropriate care to couples experiencing pregnancy loss and increase awareness among all health professionals involved in obstetric care. Further research should investigate to what extent miscarriage is included in the educational midwifery programmes, and how the current healthcare practice regarding miscarriage care is organised. Highlights: Midwives have rather a low level of knowledge on specific aspects of miscarriage. Midwives express a need for extra training. Midwives consider themselves as a key figure in providing psychosocial support. Several barriers (e.g. lack of time) hamper the provision of adequate care. Adequate training is needed to promote miscarriage care and increase awareness.